Harmonization of AASB 1010/AAS 10 Revaluation of Non-Current Assets” With AIS 16 ‘Property, Plants, and Equipment’ and the Perception of Likely Affected Parties - Ruhupatty, LeRoy Tim (JBE (Journal of Business and Economics); Volume 9 No.1, 2010 JBE UNKLAB, 2010)
In June 1998, Australian Accounting Standards (AASB) issued Exposure Draft (ED) 92 ‘Revaluation    of Non-current Assets’. ED 92 was issued with the purpose of harmonizing AASB 1010 and Australian Accounting Standards (IAS) 16 ‘Property, Plant, and Equipment’. Findings of past studies on harmonization of accounting standards suggested that accounting practices were partly influenced bu unique firm characteristics. There were several requirements proposed in ED 92 that would potentially affect Australian entities if these proposed requirements proposed in ED 92 suits Australian business environment and Australian firms. The perception of likely affected parties to ED 92 were further related to the December 1999-issued AASB 1041/AAS 38 (these standards were based on ED 92). It was found that respondents to ED 92 supported any harmonization, however, they did not support any harmonization program for the sake the harmonization program would no improve the quality, usefulness, and comparability of financial information.